ANALISIS PENGARUH WORD of MOUTH, PERSEPSI HARGA DAN KUALITAS PRODUK TERHADAP PERPINDAHAN MEREK SEPEDA MOTOR BEBEK YAMAHA KE HONDA (Studi Kasus pada Masyarakat Semarang) - Hakim, Muhammad Andie; Sutopo, Sutopo (Faculty of Economics and Business Diponegoro University, 2016)
Of the total sales of Yamaha motorcycles between 2012 and 2014 decreased, on the other hand Honda motorcycles increased, and other motorcycle brands tend to stagnate. Thus this study aims to examine and analyze the effect of word of mouth, perception of price and quality of products, on brand switching decision motorcycle Yamaha to Honda. This study uses three independent variables, word of mouth (X1), the perception of price (X2), product quality (X3) and brand switching decision as the dependent variable. The population used in this study is that consumers who have used the product Yamaha motorcycle and decided to move to the Honda motorcycle products. This research method using purposive sampling technique, which the researchers focused on respondents who had previously used Yamaha motorcycle and decided to switch to a Honda motorcycle. Used as a sample of 100 respondents. Data obtained from a questionnaire which is then processed and analyzed using multiple regression analysis through SPSS.The results showed that word of mouth has a positive effect on brand switching decision, the perception of the price has a negative influence on brand switching decisions, and product quality has a positive influence on brand switching decision.